Kaposi's sarcoma: a computational approach through protein-protein interaction and gene regulatory networks analysis - Zaman, Aubhishek M.; Rahaman, Md. Habibur; Razzaque, Samsad (© 2012 Springer Science+Business Media New York, 2016)
This article was published in Virus Genes [© 2012 Springer Science+Business Media New York ] and the definite version is available at : http://doi.org/10.1007/s11262-012-0865-z The Journal's website is at: http://link.springer.com/article/10.1007%2Fs11262-012-0865-z